Economics and retrofit - Bostenaru, M.; Mendes, D. A. (Natural and man-made hazard impact on urban areas - Impactul hazardurilor naturale ?i antropice asupra ariilor urbane, 2017)
The purpose of this mission is to explore an aspect of disaster management to which little research exists, namely the economic aspects. The topic is based on over 10 years of dealing with the subject, and while this will lead to a transfer of knowledge to the host institution, the new aspects related to the activity of the COST action IS1104 will contribute to the professional development of the grantee. The priority areas of the COST action touched are the roles of game theory, agent based modeling and to lesser extent networks and urban public policies in designing decision systems for earthquake risk management. The accent here lays mainly on game theory, and on the way cooperative action is modeled, since intervention in case of a disaster involves multiple actors. Therefore, also alternatives to game theory such as drama theory will be looked at, in a comprehensive literature review. Aim is to design which components of the real situation can be brought in the abstract (IT) model of a game to support decision making between the actors involved in decision about preventive retrofit compared to post-earthquake repair, the so-called planned conservation. The difference between the mathematical model in collaborative game theory and the architectural/urban approach of designing participative processes through games will be investigated and reported on. These aspects relate to urban policies. At the same time, the involvement of these multiple actors in the decision system links to agent based modeling. The aim of the research in this context will be setting up a comparison between the classical decision making (by means of computer supported expert opinion consulting) with computer simulated agent based modeling, drawing conclusions on the advantages and the disadvantages of the two approaches. The above mentioned drama theory and the related conflict solving software are the first part of the equation, where the balancing is done by the experts. Agent based modeling has been however successfully applied in designing resource allocation systems after an earthquake event, a moment in planning which links to the third component related to the action, the networks. In this particular field to which the proposed STSM is related street networks have been identified playing a key role. The outcome will be the respective comparison tables and the ontology of the model.